SAT0015 TREATMENT WITH ABATACEPT BUT NOT WITH TNF BLOCKERS, IS ASSOCIATED WITH A REDUCTION OF CONSTITUTIVELY ELEVATED CIRCULATING FOLLICULAR HELPER T CELLS IN RHEUMATOID ARTHRITIS. (June 2019) - Fortea-Gordo, Paula; Nuño, Laura; Villalva, Alejandro; Santos-Bornez, Maria-Jose; Peiteado, Diana; Monjo, Irene; Balsa, Alejandro; Miranda-Carus, Maria-Eugenia
Abstract : Background: Circulating CD4 T cells that express CXCR5 together with PD-1 and/or ICOS are considered as counterparts of bona fide Tfh cells and function as B cell helpers. In addition, circulating CD4+CXCR5+ T cells can be subdivided into three subpopulations: CXCR5+CXCR3+CCR6- (Tfh-Th1), CXCR5+CXCR3-CCR6+ (Tfh-Th17) and CXCR5+CXCR3-CCR6- (Tfh-Th2). Only Tfh-Th17 and Tfh-Th2 but not Thf-Th1 cells seem to provide B cell help. Altered frequencies of circulating Tfh cells (cTfh) and of cTfh cell subpopulations have been associated with autoimmune conditions. We previously described that patients with RA treated with conventional synthetic DMARDs (csDMARDs), demonstrate constitutively altered frequencies of cTfh and cTfh cell subpopulations that are observed not only in patients with an active disease but also in patients who are in remission. Objectives: To determine if treatment with biological agents (TNF blockers or abatacept) is able to modify the constitutively altered cTfh and cTfh subpopulation numbers, observed in RA patients receiving csDMARDs Methods: Peripheral blood was drawn from RA patients receiving csDMARDS (n=22), TNF blockers (n=21: 10 infliximab, 6 etanercept, 3 certolizumab, 2 adalimumab), or abatacept (n=17). For each patient, an age and gender-matched healthy control was also studied (n=60). cTfh and plasmablast frequencies were determined by flow cytometry of freshly isolated PBMCs. Results: As described, RA patients receiving csDMARDs demonstrated, whether they had an active or inactive disease, an increased frequency of CD4+CXCR5+PD-1 hi and CD4+CXCR5+ PD-1 hi ICOS+ T cells, together with an increased frequency of circulating plasmablasts. In addition, the frequency of Tfh-Th1 cells was significantly decreased and the frequency of Tfh-Th17 and Tfh-Th2 cells were significantly increased as compared with HC; subsequently, the ratio (Tfh-Th17+Tfh-Th2)/Tfh-Th1 was increased in RA: that is, RA patients demonstrated a higher proportion of Tfh cell subsets bearing a phenotype associated with B cell helping capacity. Interestingly, these alterations were also observed in RA patients treated with TNF blockers, whether they had an active or inactive disease. In contrast, in patients receiving abatacept, the frequencies of cTfh, cTfh cell subpopulations and plasmablasts, were not different from those observed in HC. Conclusion: Patients with RA receiving csDMARDs or TNF blockers demonstrated a constitutively increased frequency of cTfh cells and an overrepresentation of cTfh subsets bearing a B cell helper phenotype, suggesting that altered germinal center dynamics play a role in RA pathogenesis. Remarkably, in RA patients treated with abatacept these frequencies and ratio were not altered, indicating that costimulation blockade is able to revert the increased generation of Tfh cells in RA; conversely, TNF neutralization does not seem to affect the generation or recirculation of cTfh. Reference: [1] Simpson Net al, Arthritis Rheum 2010; Craft J, Nat Rev Rheumatol 2012; Morita R, et al., Immunity 2011; Arroyo-Villa I, et al., Arthritis Res Ther 2014. Disclosure of Interests: Paula Fortea-Gordo: None declared, Laura Nuño: None declared, Alejandro Villalva: None declared, Maria-Jose Santos-Bornez: None declared, Diana Peiteado: None declared, Irene Monjo: None declared, Alejandro Balsa Grant/research support from: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Consultant for: Abbvie, Pfizer, Novartis, BMS, Nordic, Sanofi, Sandoz, Lilly, Paid instructor for: Pfizer, Speakers bureau: Pfizer, Novartis, UCB, Nordic, Sanofi, Sandoz, Lilly, Maria-Eugenia Miranda-Carus Grant/research support from: Roche Pharma, BMS